Sinonasal methicillin-resistant Staphylococcus aureus: updates on treatment. Issue 1 (February 2017) - Al-Asousi, Fahad; Dadgostar, Anali; Javer, Amin
Abstract : Purpose of review: Over the past two decades, the management of methicillin-resistant Staphylococcus aureus (MRSA) in chronic rhinosinusitis has posed significant challenges. This document reviews current management techniques and novel treatment modalities for sinonasal MRSA infections. Recent findings: Topical antibiotic therapy, that is, drops (ofloxacin) and ointments (mupirocin) as off-label use for the management of MRSA chronic sinusitis, has shown beneficial results. Other more recently trialed nonantibiotic modalities such as antimicrobial photodynamic therapy and colloidal silver irrigation are also showing promise. Summary: Sinonasal MRSA is considered to be associated with recalcitrant chronic sinusitis. Advancements in systemic and local antibiotics in its management have been slow and unsatisfactory. Attention is shifting to the use of nonantibiotic antibacterial treatments. Knowledge of these options is critical to improve the overall management of these chronic patients.